The 2019 Conference on Artificial Life 2019
DOI: 10.1162/isal_a_00226
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Escape-based Flocking behavior using Multi-Agent Reinforcement Learning

Abstract: In nature, flocking or swarm behavior is observed in many species as it has beneficial properties like reducing the probability of being caught by a predator. In this paper, we propose SELFish (Swarm Emergent Learning Fish), an approach with multiple autonomous agents which can freely move in a continuous space with the objective to avoid being caught by a present predator. The predator has the property that it might get distracted by multiple possible preys in its vicinity. We show that this property in inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Further, Sunehag et al (2019) find the emergence of flocking and symbiosis with rewards shaping by independent MARL in simulated multiple-species ecosystems. In parallel, Hahn et al (2019) demonstrate the emergence of swarming without reward shaping and later show that in their scenario, prey swarming is a Nash Equilibrium (Hahn et al, 2020) and the prey could perform better if collectively fleeing independently. Ritz et al (2020) also found independently fleeing prey to be significantly harder to hunt for a single RL predator.…”
Section: Further Emergent Behaviormentioning
confidence: 91%
See 1 more Smart Citation
“…Further, Sunehag et al (2019) find the emergence of flocking and symbiosis with rewards shaping by independent MARL in simulated multiple-species ecosystems. In parallel, Hahn et al (2019) demonstrate the emergence of swarming without reward shaping and later show that in their scenario, prey swarming is a Nash Equilibrium (Hahn et al, 2020) and the prey could perform better if collectively fleeing independently. Ritz et al (2020) also found independently fleeing prey to be significantly harder to hunt for a single RL predator.…”
Section: Further Emergent Behaviormentioning
confidence: 91%
“…Regarding the agents, the prey strategies proposed by Hahn et al (2019) were compared in preliminary experiments (c.f. Figure 2a).…”
Section: Methodsmentioning
confidence: 99%
“…Multi-agent reinforcement learning (MARL) has become popular to model individually rational agents in SDs and SSDs to examine emergent behavior [6,23,31,15,36]. The goal of each agent is defined by an individual reward function.…”
Section: Introductionmentioning
confidence: 99%
“…After the decentralized planning procedure is over, the trained policy is reintegrated into the method. Hahn et al [ 32 ] proposed Swarm Emergent Learning Fish (SELFish), a reinforcement learning approach to evolve prey animals based on predation. For the multi-agent concept, every individual agent optimizes its own behavior without any centralization or integration.…”
Section: Introductionmentioning
confidence: 99%